Teori Marxis: Konsep, Sejarah, dan Pokok-Pokok Pemikiran Karl Marx - Ivan Maulana Yusuf (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Marxist theory is one of the classical social theories that provides an analytical foundation for understanding the social and economic dynamics of society. This theory emphasizes that social, political, and cultural structures do not stand independently, but are shaped by the system of production and the underlying economic relations. Within this theoretical framework, human history is viewed as the history of struggles between social classes. This paper elaborates in depth on the definition of Marxist theory, its founding figures, the historical background of its emergence, the main ideas developed by Karl Marx, and the relevance of his theory in the modern context. Through this discussion, it is expected that readers will understand that Marxist theory is not merely a scientific analysis, but also a form of social critique against inequalities arising from the capitalist system.